Chapter Puer bonus communicandi peritus. Esercizi e strumenti per dibattere tra pari - Simonetta, Gianluca (Communication and Philosophical Cultures. Researches and Instruments, 2021)
The peer learning project RApP (Ragazze e Ragazzi apprendono tra Pari) took place at the ISIS Gobetti-Volta high school in Bagno a Ripoli, Florence. With the aim to develop debate and public speaking activities, the project applies the IDEAM method, known as the five canons of ancient rhetoric (Inventio, Dispositio, Elocutio, Actio and Memoria). Thanks to this framework, it is possible to visualize and apply changes to the organization and writing of an effective speech, as well as to its memorization and delivery in public. A platform of applied training combined with a set of propaedeutic exercises based on the approach of ancient progymnasmata outlines a gradual pathway aimed at strengthening the uses of language as an individual skill, with a view to acquiring the skills to use language in the social environment of debate.